Steppe dreams : time, mediation and postsocialist celebrations in Kazakhstan - Adams, Margarethe (Pittsburgh : University of Pittsburgh Press, 2020)
Steppe Dreams concerns the political significance of temporality in Kazakhstan, as manifested in public events and performances, and its reverberating effects in the personal lives of Kazakhstanis. Like many holidays in the post-Soviet sphere, public celebrations in Kazakhstan often reflect multiple temporal framings--utopian visions of the future, or romanticized views of the past--which throw light on present-day politics of identity. Adams examines the political, public aspects of temporality and the personal and emotional aspects of these events, providing a view into how time, mighty and unstoppable, is experienced in Kazakhstan.
Setting the scene : a musical map of Almaty -- Airing independence : performing the past and the future on December 16 -- Same time next year : winter and rhythmicity on television -- An archaeology of Nauryz : the ancient past in public culture -- Traveling histories : ethnicity, mobility, and religion in spring celebrations -- Playing at war : musical commemorations of World War II on May 9 -- The precarious present and the city of the future : Astana, Islam, and pilgrimage -- Conclusion. Striking the set.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO; viewed June 8, 2020)
JSTOR
Keywords: Kazakhstan -- Civilization; Kazakhstan -- Anniversaries, etc; HISTORY -- General; Civilization; Anniversaries; Kazakhstan